Prevalence of Social Phobia among Students at Kufa Technical Institute - Hadi Y. Al-Mussayi; Arafat Al-Dujaily (Kufa Journal for Nursing Sciences)
Background: Social phobia is a highly prevalent disorder in western countries, but is rather rare in eastern societies. Prevalence rates range between 0.5% in eastern studies and up to 16% in western studies.